1993
DOI: 10.1177/152808379302200409
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Adhesion Mechanisms Between PVC Coatings and Different Textile Substrates

Abstract: The adhesive bonds between a PVC coating and its fabric substrate are affected by the hydrophilic character of the material and the environmental condi tions under which the coating process is carried out. Work has been carried out at TEFO for the purpose of studying the influence of different sources of moisture on adhesion between PVC coating and substrates of polyester, nylon-based woven and knitted structures, and PES film. The results have been evaluated in accordance with the newly developed TEFO method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…The adhesion of polymer coatings to substrates has been the subject of two recent papers [49][50]. Investigations are also being conducted into the use of ultraviolet laser irradiation to etch the surface of synthetic filaments to provide mechanical bonding [49,[51][52]].…”
Section: 1 Adhesion Of Coating To Synthetic Filament Yarnsmentioning
confidence: 99%
“…The adhesion of polymer coatings to substrates has been the subject of two recent papers [49][50]. Investigations are also being conducted into the use of ultraviolet laser irradiation to etch the surface of synthetic filaments to provide mechanical bonding [49,[51][52]].…”
Section: 1 Adhesion Of Coating To Synthetic Filament Yarnsmentioning
confidence: 99%
“…Their basic components are as follows: PVC resin, a stabilizer, a plasticizer, a blowing agent, and a filler [ 8 ]. Plastisol is made by evenly mixing these components [ 9 , 10 ]. Fillers are especially utilized to reduce the cost of the final product.…”
Section: Introductionmentioning
confidence: 99%
“…Polyvinyl chloride (PVC) coating is seldom used to apply as industrial coatings because their difficulty on adjusting the optimum coating process parameters. Most of the case study ended up with the failure on deposition of PVC on metal substrate and revealed the degradation zone as the defected area [5].…”
Section: Introductionmentioning
confidence: 99%